Peningkatan Vokasional Menjahit Busana Etnik melalui Direct Instruction bagi Anak Tunarungu - Khairunnisa, Karmila; Nurhastuti, Nurhastuti (Jurnal Penelitian Pendidikan Khusus, 2022)
Giving vocational lessons for deaf children helps children in improving their ability to learn skills that will be useful in the future as skills that can be used to earn a living if implemented optimally. This research is entitled "Improvement of Vocational Sewing Ethnic Clothing through Direct Instruction for Deaf Children (Classroom Action Research Class X at SLBN Padangsidimpuan)"This type of research is a type of classroom action research (CAR), with the aim of knowing how to improve children's vocational sewing with the direct instruction method. This research was conducted in collaboration with the teacher as the executor of the action. From the results of the study, it was found that the increase in sewing ethnic clothing ,vocational, namely the initial ability of students from AS 50%, and TS 50%, then given action in the first cycle increased to AS 61%, and TS 58%, then continued in the second cycle the child's ability increased to US 91%, and TS 83%.